Incorporating Islamic Ethic Elements into Marketing Mix Paradigm - Shafin, Nazree; Kasim, Rozilah (Financial Risk and Management Reviews, 2019)
To consider the extent to which the dynamism of ethic elements from four commendable characteristics of Prophet Muhammad (PBUH) fits within existing marketing mix framework thinking in strengthening marketing mix approach of Islamic business. This can be achieved through analyzing selected elements of Islamic ethic features, that are derived from the four (4) commendable characteristics of the Prophet Muhammad (PBUH): Siddiq (Truthfulness), Amanah (Trustworthiness), Fathanah (Wisdom), and Tabligh (Advocacy), abbreviated as “SAFT to be incorporate as a catalyst to strengthen the marketing mix approach and thus propose a practical Islamic Marketing Mix as a competitive marketing tactic. Analytical and comparative analyses are used and study reveals four ethic elements in Islamic perspective that can be potential elements in developing a practical Islamic Marketing Mix for any business whether Islamic or non-Islamic.